Preference shooping mall in Penang Island by using GIS application / Fatin Hanisah Hashim - Hashim, Fatin Hanisah (2019)
People nowadays want a quick and easy life. With the evolution of technology, people want something that gave an easy life for them To help in achieving that, this study is done in hope it can help people to have a good planning trip especially in congested area. Map is considered as one of tool which is important to provide information of certain places. The data that will be provided in GIS map application may provide the useful information for the public users, thus can give contribution to Penang Island in context of tourism and economy. The aim of this study is to produce an application consists o f map of Penang Island includes path and hotspot shopping malls by using GIS analysis. By going through five crucial stages starting from planning stage, data collection stage, data processing stage, data analysis stage and data visualization stage, the aim has been achieved.